A Study on Youth Behavior towards the North Vidzeme Biosphere Reserve in Latvia - MEZGAILE, Anda; GRINBERGA, Kristine; SINGH, Nripendra; LIVINA, Agita (Journal of Environmental Management and Tourism, 2021)
This paper reports the results of a study of young visitors’ intentions to visit the North Vidzeme Biosphere Reserve in Latvia (target audience Generation Z and Generation Y, 15–25-year-old youth—the oldest part of the Generation Z and the younger part of Generation Y have been studied). The integrated research method was used: an online survey was conducted for data collection (n=317) and focus group discussions and observations (three groups—two from Latvia and one from Estonia) were held to study youth traveling behaviour in the North Vidzeme Biosphere Reserve. Findings showed that most youth are highly motivated to visit biosphere reserve by push and pull factors and agreed that visiting the biosphere reserve relieves stress, helps them to socialize, and allows them to escape from their daily routine. Almost all respondents agreed that there was a lack of advertisements, information in foreign languages and visibility of the area, but they also stated that they would be more motivated to visit and revisit the biosphere reserve if they could see their friends visiting it and posting about it on social media. Research pointed out that there is significant difference between Generation Z and Generation Y in platforms used for searching for information, as well as required tourism infrastructure elements.